2017
DOI: 10.3892/etm.2017.4351
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Botox-A SNAP-25 protein expression and the mechanism of inhibitory neurotransmitter imbalance in chronic sciatic nerve pain rat model

Abstract: The Botox-A impact on the expression of SNAP-25 protein in rat chronic sciatic nerve pain model was assessed and the mechanism of inhibitory neurotransmitter imbalance was studied. A chronic constriction injury (CCI) model consisted of 30 healthy male rats. The rats were randomly divided into the sham-operated group, CCI group and BoNT/A intervention group, and during 1, 7 and 14 days we conducted mechanical withdrawal threshold (MWT) test and thermal withdrawal latency (TWL) test before and after operation. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…This finding is significant as previous studies demonstrated that SNAP25 contributed to neuropathic pain [ 12 ]. It was reported that overexpression of SNAP25 in rats induced pain-responsive behaviors and that breaking down SNAP25 by using botulinum toxin A relieved mechanical allodynia and neuropathic pain after peripheral nerve injury in rat models [ 12 14 ]. Through drug-gene interaction analyses, the present study found that botulinum toxin and its derivatives are potential drugs for treating neuropathic pain by targeting SNAP25.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is significant as previous studies demonstrated that SNAP25 contributed to neuropathic pain [ 12 ]. It was reported that overexpression of SNAP25 in rats induced pain-responsive behaviors and that breaking down SNAP25 by using botulinum toxin A relieved mechanical allodynia and neuropathic pain after peripheral nerve injury in rat models [ 12 14 ]. Through drug-gene interaction analyses, the present study found that botulinum toxin and its derivatives are potential drugs for treating neuropathic pain by targeting SNAP25.…”
Section: Discussionmentioning
confidence: 99%